PENGARUH STRUKTUR MODAL, LIKUIDITAS, PERTUMBUHAN LABA, UKURAN PERUSAHAAN DAN INVESMENT OPPORTUNITY SET (IOS) TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Redy Arisonda (STIE AUB Surakarta, 2018)
This study is to provide empirical evidence of the significant influence of capital structure, liquidity, profit growth, firm size, and dan Invesment Opportunity Set (IOS) on earnings quality in manufacturing companies listed on the IDX. The population of this study is all manufacturing companies listed on the Stock Exchange. Data collection methods in this study are taken from the internet stock exchange pages of financial statements in 2015-2017. The analysis technique consists of descriptive analysis, classical assumptions and multiple linear regression, t test, and coefficient of determination (R2). The results of the analysis show that the validity and reliability of all the questions asked are valid and reliable. The results of the classical assumption test showed that this study was normally distributed, there was no multicollinearity, autocorrelation and heterocedasticity in the regression model. The results of multiple linear regression test prove that capital structure, liquidity, profit growth and investment opportunity set have a positive effect on the quality of corporate earnings and firm size variables negatively affect earnings quality. The results of the t test show that the size of the company and investment opportunity set have a significant effect on earnings quality and capital structure variables, liquidity, and earnings growth have no significant effect on earnings quality.Keyword: capital structure, liquidity, profit growth, company size, investment opportunity set and earnings quality.